A Potensi Nugget Bakar Ikan Belanak dan Formula Tempe (Bellforte) sebagai Snack Alternatif Penderita TB-Paru melalui Uji Organoleptik dan Mutu Kimia: Potential of Mullet Gilled Nuggets and Tempeh Formula (Bellforte) as an Alternative Snack for Patients with Pulmonary TB through Organoleptic and Chemical Quality Tests - Ginta Siahaan; Sri Heriyanto; Zuraidah Nasution; Dini Lestrina; Efendi Nainggolan; Khoiriyyah Khoiriyyah; Sakinatussyifa Siregar (Amerta Nutrition, 2026)
Background: Pulmonary Tuberculosis (TB) is an infectious disease that remains a serious global concern and is among the leading causes of death worldwide, according to the 2021 World Health Organization (WHO) report. More than 4,100 people die from Pulmonary TB each day, highlighting the need for comprehensive management through pharmacological therapy and the High-Energy High-Protein Diet (HEHPD). An approach to support treatment success is developing nutrient-dense snacks, such as nuggets, to improve nutritional value and reduce patients’ boredom during treatment Objectives: To determine the organoleptic test and chemical quality test of grilled mullet fish and tempeh formula (Bellforte) nugget. Methods: A Completely Randomized Design (CRD) was used with 4 compositions and 2 repetitions involving 60 panelists and 10 panelists who were Pulmonary TB patients in the working area of the Lubuk Pakam Community Health Center. The selected composition underwent an examination of its protein, albumin, iron, and zinc levels. Data analysis was conducted using the SPSS statistical application version 22. Results: Composition B was the selected nugget composition as the most preferred, with a slightly brownish-yellow color, slightly chewy texture, savory fish taste, and distinct fish aroma, containing 12.11 g of protein with a 19 % contribution (high), 0.153 g of iron with a 1.3 % contribution, 2.2 mg of zinc with a 23 % contribution, and 6.45 g of albumin. Conclusions: The Bellforte nugget Composition B is organoleptically acceptable as a snack food, and the chemical test results indicate that the nutrient contribution meets the 10 % snack standard.